SOCIAL MEDIA AND TEENS’ SELF-CONCEPT: A SYSTEMATIC LITERATURE REVIEW - Sarita Rizki; Tukma Putri Anti (Madiha Press, 2025)
Social media has emerged as a global phenomenon, profoundly shaping various dimensions of life, including the self-concept of Indonesian teenagers. This study presents a systematic review of literature that investigates the influence of social media on adolescents' self-concept within the unique cultural framework of Indonesia. Conducted following PRISMA guidelines, the review employed comprehensive searches in databases such as Google Scholar and ERIC. Findings from the 20 articles selected upon abstract and full article reviews reveal that social media affects self-concept through mechanisms such as social comparison, identity expression, and peer validation, with Indonesian cultural norms amplifying these dynamics. The review highlights both positive outcomes, such as enhanced self-expression and social support, and negative effects, including body dissatisfaction, anxiety, and reduced self-esteem, depending on factors like usage frequency and content type. A critical analysis of included studies identifies key moderators, including digital literacy and familial support, while offering actionable recommendations to mitigate risks and optimize benefits. By uncovering research gaps, this review provides a roadmap for future studies and interventions tailored to Indonesia’s cultural context.